The relationship between digital technologies and internationalisation. Evidence from Italian SMEs. Issue 4 (20th April 2020) - Cassetta, Ernesto; Monarca, Umberto; Dileo, Ivano; Di Berardino, Claudio; Pini, Marco
ABSTRACT: The article empirically explores the role of e-business digital technologies in explaining the export propensity of Italian SMEs and focuses on the adoption and implementation of e-business technologies that enable firms to share information along the supply chain in order to take into account potential heterogeneities in paths of digitalisation. Our results, besides confirming the positive role of internet-based technologies already investigated in the current literature, show that e-business technologies have a positive impact on internationalisation only when they are embedded within process and organisational innovations and investments in digital skills have been made. This indirectly supports the argument that as the array of technological choices increases, the need for concurrent internal changes, as well as a detailed assessment of the connectedness between technological alternatives and specific business types, industries, or trading environment become increasingly important.